Compare the Effectiveness of a Peel-Off Mask and Sheet-Mask with Green Tea Extract on Dermapen-Treated Wounds on the Back Surface of Female Wistar Rats - Henny Hajaratul Aswat; Lenni Dianna Putri; Andri Hidayat (Newinera Publisher, 2024)
Microneedling has recently been cited as having high efficacy, safety, and recovery rates post-treatment. This microneedling procedure has shown results that increase patient satisfaction and awareness of doctors who want minimal treatment but still get maximum results for healing uneven skin on the face and acne scarring. The test and analysis of the difference in effectiveness between the use of a peel-off mask and a sheet mask in healing wounds treated with derma pen on the surface of the back skin of female Wistar rats (Rattus norvegicus). This research approach uses experimental quantitative research methods, namely an actual experiment or laboratory experimental design. They used a pre-test – post-test control group design to determine and analyze the differences or comparisons in the effectiveness of using a peel-off mask and a sheet mask for wounds treated with a derma pen on the skin surface. The research subjects were 10 female Wistar rats (Rattus norvegicus). The research procedure was the acclimation of test animals, phytochemical screening, treatment, and observation carried out on mice by administering dermapen wounds. The research data was analyzed using the SPSS program. In this study, Wistar strain white rats (Rattus norvegicus) with peel-off and sheet masks healed their wounds. Dermapen wounds heal after 14 days, as the average rat wound length shows. The peel-off mask group healed 100% on day 13, while the sheet-mask group healed 100% on day 12. Based on this percentage difference, the researchers found that the group with the fastest wound healing used a 12-day green tea sheet mask.